2006
DOI: 10.1002/mus.20614
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the gastrocnemius muscle of undernourished suckling rats

Abstract: Protein-energy undernutrition (PEU) during both the gestational and suckling periods causes a reduction in muscle fiber cross-section and a delay in fiber type differentiation. Such changes are not found when PEU occurs after the suckling period. To elucidate the consequences of PEU on muscle during the suckling period, we undernourished (UND) newborn rats by reducing their food intake, including a 6-hour fast every day, and doubling the number of pups suckled by the nursing rat. At day 24 of life, the gastroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Some muscle fibers are not completely formed at birth and are considered undifferentiated. These primitive muscle fibers are known as fetal or type IIc fibers, and are smaller than the remaining fibers …”
mentioning
confidence: 99%
“…Some muscle fibers are not completely formed at birth and are considered undifferentiated. These primitive muscle fibers are known as fetal or type IIc fibers, and are smaller than the remaining fibers …”
mentioning
confidence: 99%
“…Other studies with rats subjected to protein restriction have also reported a smaller areas in all fiber types (Nascimento et al, 1990;Silvado & Werneck, 2006;Yan et al, 2012). The literature indicates that protein restriction can compromise the area of type II fibers more than that of type I fibers (Bedi et al;Chopra et al, 1987;Wilson et al, 1988;Dwyer & Stickland, 1992;Oliveira et al;Alves et al).…”
Section: Discussionmentioning
confidence: 79%
“…A number of studies have demonstrated that malnutrition is able to alter muscle development and structure. 28,29 Through the analysis of biomechanical aspects of muscle, it was found that malnutrition can alter muscular performance in adult rats, even when imposed for short periods, by altering characteristics such as tension, relaxation and fatigue. 30 It remains to be seen whether the elastic properties of tendons and other structures linked to the muscle spindles are also altered by malnutrition, contributing to the lower T-reflexes.…”
Section: Figure 3 Mean ± Sd Of the T Max /M Max Ratio During The Matumentioning
confidence: 99%